USM SIGNS MoU WITH NOVATEC IMMUNDIAGNOSTICA GmbH, GERMANY - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 5 May 2017 – Universiti Sains Malaysia (USM) through the Institute for Research in Molecular Medicine (INFORMM) signed a Memorandum of Understanding (MoU) with NovaTec Immundiagnostica GmbH (NovaTec), Germany on collaborating for the commercialisation of diagnostic products.